Microstructures, properties, and applications of laser sintered 17‐4PH stainless steel. Issue 9 (25th February 2019) - Irrinki, Harish; Nath, Subrata Deb; Alhofors, Magnus; Stitzel, Jason; Gulsoy, Ozkan; Atre, Sundar V.
Abstract: The effects of hot isostatic pressing (HIP) on the densification, mechanical properties, and microstructures of laser‐powder bed fusion (L‐PBF) 17‐4 PH stainless steel parts were studied using gas‐ and water‐atomized powders. The % theoretical density, ultimate tensile strength, yield strength, elongation, and hardness of as‐printed and HIP‐ed L‐PBF parts were sensitive to energy density and starting powder shape, size, and type. At low‐energy densities of 64 and 80 J/mm 3, densification was significant for water‐atomized L‐PBF parts when subjected to HIP treatment and density increased from 90% to 97%. For all the energy densities, the gas‐atomized L‐PBF parts after the HIP treatment showed significantly higher tensile strength, yield strength, and hardness when compared to water‐atomized L‐PBF parts properties. At low‐energy densities of 64 and 80 J/mm 3, long columnar grains in the as‐printed L‐PBF parts did not change significantly after the HIP treatment whereas the columnar grains present in as‐printed gas‐atomized L‐PBF parts completely disappeared when subjected to HIP treatment. However, at high‐energy densities of 84 and 104 J/mm 3, the columnar grains in as‐printed L‐PBF gas‐ and water‐atomized L‐PBF parts were changed to equiaxed grains and showed a higher level of homogenization when subjected to HIP treatment. This variation in grains and grain size had significantly affected the yield strength and elongation of HIP‐treated gas‐ and water‐atomized L‐PBF parts.